Overcoming cultural taboo: A qualitative study of the untold lived experience of older adults’ sexual life in Cebu, Philippines - Marjorie R. Sta. Teresa; Alain Kenneth S. Ragay; Alberich F. Machacon (Belitung Nursing Journal)
Background: The craving for sexuality and closeness continues into old age, although the means of expressing it may change. Beyond direct sexual encounters, older adults can express their sexuality through gentle affection, warm embraces, holding hands, and other intimate gestures. However, aging can also impact their sexual experiences.